Rôle of Thrombin in Prothrombin Activation - Seegers, W. H; Schröer, H; Heene, D (Thrombosis and Haemostasis, 1964)
The partial thromboplastin time and purified thrombin were used to demonstrate the procoagulant power of thrombin. Only 0.007 μg of thrombin could be detected in prothrombin activation. Traces of thrombin and autoprothrombin C can fully account for the generation of procoagulant activity in the thromboplastin generation test. Inactivation of these two activities by antithrombin explains the disappearance of the procoagulant power in that test, so that there now remains no valid demonstration of the existence of plasma thromboplastin or of anti-plasma thromboplastin.